PENGARUH SENAM NIFAS TERHADAP PROSES INVOLUSI UTERI PADA IBU POSTPARTUM - Ika Nur Saputri; Rahmad Gurusinga; Nurmailaini Friska (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2020)
Postpartum hemoragic is caused by unfavorable uterine involution, therefore early ambulation with puerperal gymnastics is necessary. Puerperal gymnastics is one way for early mobilization that is highly recomended for post partum mothers so that the process of involution is smooth. The purpose of the study was to determine the effect of puerperal gymnastics by uterine involution in post partum in midwife clinick Nining Pelawati in lubuk pakam sub-district with terrain city in 2019. The research medhod is a pre-experiment with respondent totaling 30 normal post partum mothers at the seka sriwahyuni midwife clinic consisting of 15 morhers who performed puerperal gymnastics (eksperimental respondent group). And 15 mothers who did not do purperal gymnastics (group of control respondents). Data collection uses observation while the formula uses the dependent t-test, the results of the study of the speed of uterine involution in mothers who do puerperal gymnastics are mostly in the fast category as much as 8 people (53,3%), the rest are in the normal categori as many as 5 people (33,3%), while those in the slow category do not exit (0,00%). The rate of uterine involution in pospartum women who do not do partuirition gymnastics in the majority in the slow category in 9 people (60,6%), the rest are in the normal category as 4 people (26,6%), while in the fast category as many as 2 people (13,3%). It can be concluded differences in changen in uterine involution between intervention groups ang control groups.